Limitation the use of Laptops when Online Learning Reduce the Eye Fatique of Private Junior High School Students in Denpasar - Biomi, Agnes Ayu; Kusuma, Made Adhyatma Prawira Natha; Kilimandu, Behar (International Journal of Natural and Health Sciences, 2024)
The emergence of eye fatique in junior high school students during the online learning process is caused by the length of time the eyes stare at the laptop for a long time. In addition, the presence of more sophisticated learning media, the position of the laptop is very important and has a main function in supporting the online learning process. From a preliminary study conducted on 10 students from a private junior high school in Denpasar, it was found that 50% of students experienced complaints of dizziness, 50% glare and 20% sore eyes. With the above background, a study with the same subject design was conducted involving 25 students with an age range of 13-14 years. The study was conducted for 3 consecutive days, namely on Tuesday, Wednesday and Thursday by measuring eye fatigue using an eye fatigue questionnaire. The data were analyzed using the t-paired test at a significance level of p = 0.005. After using the laptop was limited according to the radiation exposure time from the appropriate laptop, the eye sight distance to the monitor screen was set 50-100 cm and interspersed with pauses or rest periods then the average eye fatigue in students before the improvement of 22.54 can be reduced to 5.25 or about 71%. Conclusion: From the research, it was concluded that limiting the duration of using laptops during online learning can reduce students' eye fatigue